Cover Image, Volume 530, Issue 8. Issue 8 (30th March 2022) - Northington, Frances J.; Kratimenos, Panagiotis; Turnbill, Victoria; Flock, Debra L.; Asafu‐Adjaye, Daniella; Chavez‐Valdez, Raul; Martin, Lee J.
Abstract : The cover image is based on the Research Article Basal forebrain magnocellular cholinergic systems are damaged in mice following neonatal hypoxia‐ischemia by Frances J. Northington et al., https://doi.org/10.1002/cne.25263 .